Randomized Clinical Trial Comparing The Effect Of Oral Rehydration Therapy With And Without Racecadotril In The Management Of Acute Diarrhea In Children - Sughra Zulfiqar; Hifza Zeb; Nadia Mumtaz; Ammara Musthaq Khan; Taimur Khalil Sheikh; Tariq Saeed (Journal of Rawalpindi Medical College)
Objective: This study aimed to investigate the beneficial effect of racecadotril in children with acute diarrheal illness.